Factors Affecting Choices of Land Tenure in Sigi District - Amriany Amir; Lien Damayanti; Masyuri Masyurii; Any Suryantini (AGROLAND The Agricultural Sciences Journal (e-Journal), 2014)
Land tenure can be used as an illustration of equity control of the main production factors in the agricultural sector. Changes in agricultural land tenure structure will affect agricultural production (farming) both in terms of efficiency and farm income, while the pattern of land ownership represents the state ownership of the main production factors in agricultural production. The purpose of this study was to analyze the factors that influence the choice of tenure to the use of inputs, attitudes, motivation, work ethic, production and income. The research location is determined by using purposive sampling method, i.e. selecting the study area based on the characteristics or specific reasons are deemed to have a close relationship with the problems examined. The selected area in this study was Sigi District where became one of the centers of rice production, furthermore Subdistrict Gumbasa have been selected because as one of the centers of rice production also has the status of land tenure are more varied in Sigi District. The District Gumbasa selectived 2 Villages where has the highest number of rice farmers such as the Pakuli and Kalawara Village. Respondents in this study amounted to 99 respondents. Factors that affect the status of tenure choice can significantly increase the probability of tenure including the production, input prices, output prices, household income and work ethic, while the factors that were not affect the land tenure were motivation, use of labor and attitudes of farmers.